Optimal Staging and Single-Stage Arthroscopic Management Protocols for Combined ACL/PCL or Posterolateral Corner Injuries: A Prospective Clinical Study - Dr. K. Jeevan Ravi; Dr. Chandrashekhar P.; Dr. Banarji B.H.; Dr. Akshay Shetty (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background: Combined anterior cruciate ligament (ACL), posterior cruciate ligament (PCL), and posterolateral corner (PLC) injuries are technically demanding and may result in persistent multidirectional instability, stiffness, and loss of activity. The preferred timing of reconstruction and the role of single-stage treatment remain debated. Objective: To evaluate functional recovery, objective stability, range of motion, complications, and timing associations following protocol-based single-stage management of combined ACL/PCL or cruciate-PLC injuries. Methods: This prospective, single-centre interventional study included 40 adults with ACL+PCL, ACL+PLC, PCL+PLC, or ACL+PCL+PLC injuries. All underwent single-stage arthroscopic cruciate reconstruction, with PLC repair or reconstruction when indicated, followed by structured phase-based rehabilitation. Lysholm, subjective International Knee Documentation Committee (IKDC), and Tegner scores were compared before surgery and at final follow-up using the Wilcoxon signed-rank test. Spearman correlation assessed associations between injury-to-surgery interval and final outcomes. Results: Mean age was 30.75±8.75 years, and 27 (67.5%) patients were men. Road traffic or motorcycle trauma accounted for 19 (47.5%) injuries. Mean injury-to-surgery interval was 5.35±2.60 weeks, and mean follow-up was 19.95±2.84 months. Lysholm score improved from 29.15±5.61 to 88.15±5.18, subjective IKDC from 31.10±5.30 to 84.68±5.32, and Tegner score from 2.00±0.78 to 6.45±1.47 (all p<0.001). Objective IKDC grade A or B was achieved in 34 (85.0%) patients. Nine (22.5%) patients had a recorded complication, most commonly arthrofibrosis. Longer time to surgery correlated with lower postoperative Lysholm (ρ=-0.699), IKDC (ρ=-0.681), and Tegner scores (ρ=-0.669), and with greater motion loss (all p<0.001). In the exploratory ≤6-week versus >6-week comparison, the earlier group had better final scores but was also substantially younger and had higher baseline function. Conclusion: Protocol-based single-stage treatment produced substantial functional improvement and acceptable objective stability at short- to mid-term follow-up. The observed timing relationships were confounded and do not establish an optimal operative threshold or superiority over staged reconstruction.